Examining the underpinnings of psychosocial safety climate in organizations: A crafting and identity perspective - Philipp Hubert; Sascha Etgen; Andreas Mojzisch; Malte Roswag; Jan Alexander Häusser (Journal of Occupational and Organizational Psychology, 2025)
There is mounting evidence that psychosocial safety climate (PSC) is positively associated with employees' mental well-being and negatively associated with burnout. Drawing on a crafting perspective, we hypothesized that these relationships are mediated by both on-job and off-job crafting. We further hypothesized that organizational identification moderates the relationship between PSC and crafting, constituting a first-stage moderated mediation model. In a pre-registered, time-lagged study with three measurement waves, we collected data from 266 employees. As predicted, PSC was positively related to mental well-being and negatively to both disengagement and emotional exhaustion. Supporting our hypotheses, on-job crafting mediated the relationships between PSC and mental well-being, and between PSC and disengagement, but not emotional exhaustion. Off-job crafting, in turn, mediated the relationships between PSC and both well-being and emotional exhaustion, but not disengagement. Although organizational identification did not moderate indirect effects via on-job crafting, it did moderate the mediation pathways through off-job crafting for both mental well-being and emotional exhaustion, but not disengagement. In conclusion, our study advances PSC research by integrating a job crafting lens and by identifying organizational identification as a key boundary condition influencing PSC's effectiveness.
Keywords: 650; burnout; crafting; off-job crafting; on-job crafting; organizational identification; psychosocial safety climate